From the scene to the spectator: a new look at Jogo de Cena - Oliveira Teixeira de Carvalho, Helena (2024)
Eduardo Coutinho is one of the main names in Brazilian documentaries and has already been widely discussed by researchers and cinephiles. However, Consuelo Lins (2013) highlights that much of this critical thinking focused on the formal choices that the director made to construct the encounter with the characters in front of the camera, leaving the viewer in the background, as an effect of certain critical formulations. In this sense, this article proposes to investigate the spectator of Jogo de Cena from the perspective that the cinematographic operations worked on by the director create conditions of experience for the observer to submit to a process of subjectivation and to become someone else, who is neither the pre-existing subject, nor the materiality of the film, but a process in formation arising from the encounter with the film. Without this encounter, it does not exist. Based on the concepts of putting in sequence, putting in frame and putting in scene by André Gaudreault (2009), along with thoughts by authors such as Gilles Deleuze, André Bazin and Ismail Xavier, the aim is to reach a new theoretical-conceptual horizon on the great master of Brazilian documentary.